Anemia prevalence and its impact on health‐related quality of life in Indian diabetic kidney disease patients: Evidence from a cross‐sectional study. Issue 4 (25th November 2019) - Hussain, Salman; Habib, Anwar; Najmi, Abul Kalam
Abstract: Aim: The aim of the study was to determine the prevalence, predictors of anemia, and its impact on health‐related quality of life among diabetic kidney disease (DKD) patients. Methods: Patients with a confirmed diagnosis of type 2 diabetes mellitus (T2DM), and had any stages of CKD (stages I to IV), based on their estimated glomerular filtration rate (eGFR) were enrolled in the study. Anemia was defined using the World Health Organization (WHO) criteria and quality of life was assessed using the EQ‐5D scale. All the statistical analysis was performed using SAS v9.4. Results: A total of 323 patients completed the study. The mean ± SD age of patients was 56 ± 11.25 years, and 51.7% were female. Mean duration of diabetes was 9.6 ± 4.57 years. A total of 227 (70.27%) had anemia as per the WHO criteria. Linear association was observed between the eGFR and hemoglobin. After controlling for the possible confounders in multivariate logistic regression analysis, older age (odds ratio [OR]: 2.46 [95% CI: 1.16 to 5.28], P  = .021), diabetes duration (OR: 1.53 [95% CI: 1.04 to 2.25], P  = .022), and CKD stage III (OR: 3.63 [95% CI: 0.99 to 13.32], P  = .004) were found to be significantly associated with the anemia. Consistently lower EQ‐5D index values were observed for the anemic group. Conclusion: This study reported a high prevalence of anemia and impaired quality of life among DKD patients. Routine screening of anemia can be the most preventive measure to deal with this burdening co‐morbid condition.